Prices, productivity, and wage bargaining in open economies - Anders Forslund; Nils Gottfries; Andreas Westermark (Uppsala University, Department of Economics, 2008)
According to the standard union bargaining model, unemployment benefits should have big effects on wages, but product market prices and productivity should play no role in the wage bargain. We formulate an alternative strategic bargaining model, where labour and product market conditions together determine wages. A wage equation is derived and estimated on aggregate data for the Nordic countries. Wages are found to depend on unemployment and the replacement ratio, but also on productivity, international prices and exchange rates. There is evidence of considerable nominal wage rigidity. Exchange rate changes have large and persistent effects on competitiveness.
Keywords: E52; F33; F41; J31; J51; J63; J64; 330; non-cooperative bargain; efficiency wage; turnover; wage share; wage curve